Identification of a RAC/AKT-like gene in Leishmania parasites as a putative therapeutic target in leishmaniasis (2017)
ABSTARCT: Leishmaniasis is one of the world's most neglected diseases caused by at least 20 different species of the protozoan parasite Leishmania. Although new drugs have become recently available, current therapy for leishmaniasis is still unsatisfactory. A subgroup of serine/threonine protein kinases named as related to A and C protein kinases (RAC), or protein kinase B (PKB)/AKT, has been identified in several organisms including Trypanosoma cruzi parasites. PKB/AKT plays a critical role in mammalian cell signaling promoting cell survival and is a major drug target in cancer therapy. However, the role of protozoan parasitic PKB/AKT remains to be elucidated. RESULTS: We have found that anti-human AKT antibodies recognized a protein of about 57 kDa in Leishmania spp. parasites. Anti-human phospho-AKT(Thr308) antibodies identified a protein in extracts from Leishmania spp. that was upregulated following parasite exposure to stressful conditions, such as nutrient deprivation or heat shock. Incubation of AKT inhibitor X with Leishmania spp. promastigotes under stressful conditions or with Leishmania-infected macrophages led to parasite cell death. We have identified and cloned a novel gene from Leishmania donovani named Ld-RAC/AKT-like gene, encoding a 510-amino acid protein of approximately 57.6 kDa that shows a 26.5% identity with mammalian AKT1. Ld-RAC/AKT-like protein contains major mammalian PKB/AKT hallmarks, including the typical pleckstrin, protein kinase and AGC kinase domains. Unlike mammalian AKT that contains key phosphorylation sites at Thr308 and Ser473 in the activation loop and hydrophobic motif, respectively, Ld-RAC/AKT-like protein has a Thr residue in both motifs. By domain sequence comparison, we classified AKT proteins from different origins in four major subcategories that included different parasites. CONCLUSIONS: Our data suggest that Ld-RAC/AKT-like protein represents a Leishmania orthologue of mammalian AKT involved in parasite stress response and survival, and therefore could become a novel therapeutic and druggable target in leishmaniasis therapy. In addition, following comparative sequence analyses, we found the RAC/AKT-like proteins from Leishmania constitute a subgroup by themselves within a general AKT-like protein family